Predicting the power of informal learning opportunities on technology use of physical education teachers - Wibowo, Jonas; Hofmann, Rüdiger; Brand, Tabea; Wiese, Hendrik (Frontiers in Sports and Active Living, 2025)
IntroductionThis study investigates the factors influencing the acceptance of digital technologies among physical education (PE) teachers, aiming to support the integration of contemporary digital tools into movement-based learning. Drawing on the Unified Theory of Acceptance and Use of Technology (UTAUT), the research explores how contextual and personal factors shape teachers' willingness and ability to use digital technologies in their professional practice.MethodsA quantitative survey was conducted with 239 physical education teachers. The collected data were analysed using structural equation modelling (SEM) to identify relationships among the UTAUT constructs and additional variables, including formal and informal learning opportunities, age, and gender.ResultsThe analysis revealed that supportive conditions and behavioural intention equally predicted the actual use of digital technologies. Perceived usefulness and social influence significantly affected behavioural intention, whereas perceived ease of use showed no significant effect—suggesting a generally high baseline of digital literacy among the participating PE teachers. Informal learning opportunities exerted a stronger influence on performance expectancy and effort expectancy than formal learning opportunities. Age and gender were not significant predictors of technology acceptance.Discussion and ConclusionThe findings indicate that digitalisation is increasingly embedded in educational practice across demographic groups. To enhance digital technology integration in PE, stakeholders should invest in both digital infrastructure and teacher development, prioritising informal, collaborative, and practice-oriented learning environments that foster sustained technology use in movement-based education.